Patient pathways for rare diseases in Europe: ataxia as an example - Vallortigara, Julie; Greenfield, Julie; Hunt, Barry; Hoffman, Deborah; Reinhard, Carola; Graessner, Holm; Federico, Antonio; Quoidbach, Vinciane; Morris, Steve; Giunti, Paola (Orphanet journal of rare diseases, 2023)
Progressive ataxias are rare and complex neurological disorders that represent a challenge for the clinicians to diagnose and manage them. This study explored the patient pathways of individuals attending specialist ataxia centres (SAC) compared with non-specialist settings. We investigated specifically how diagnosis was reached, the access to healthcare services, treatments, and care satisfaction. The focus of this study was on early intervention, coordination of treatment to understand the care provision in different countries. A patient survey was done in the UK, Germany and Italy to gather information about diagnosis and management of the ataxias in specialist (SAC) and non-specialist settings, utilisation of other primary and secondary health care services, and patients' satisfaction of received treatment. This study provides crucial information about the ataxia patients care pathways in three European countries. Overall, the results showed a trend in patients' satisfaction being better in SAC compared to non-SAC. The outcomes can be used now for policy recommendations on how to improve treatment and care for people with these very rare and complex neurological diseases across Europe.